Design of Business Process Management in Waste Bank Application Based on BMC and SWOT Analysis - Irfan Fandi; Emil Kaburuan (CommIT (Communication and Information Technology) Journal, 2023)
Waste is one of the world’s problems that is challenging for a country or a city to do good waste management. Currently, many waste bank application providers are running to produce benefit and value for the community. However, many of them do not run optimally due to improper business processes. The research discusses the design and development of a waste bank application provider using a Business Model Canvas (BMC) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis as tools to help design a waste bank application for the provider company. The research applies a qualitative descriptive research with a qualitative approach. The sample data are taken from the waste bank application provider, PT Kompis Creative Solution using direct interviews with managers of waste bank application providers. Then, observation of the waste bank system, identification of problems, and literature studies are aimed to find information and references related to the research. The analysis indicates that the waste bank business process can be included in the BMC which can provide a neat picture for PT Kompis Creative Solution. Each of the BMC block can be the starting point for the company to determine the most important criteria. Then, the company can develop a digital waste bank strategy using the SWOT matrix to design a future strategy and minimize the risks. With the role of the waste bank application, it is expected that it improves the bank’s business processes and increases public enthusiasm to know and contribute to the mutually beneficial waste bank business.